Gelatinases (MMP-2 and MMP-9) are preferentially expressed by Th1 vs. Th2 cells - Abraham, Michal; Shapiro, Sarah; Karni, Arnon; Weiner, Howard L.; Miller, Ariel (Journal of neuroimmunology, 2005)
T helper subsets, Th1 and Th2, which are associated with different types of immune reactions, are distinguished by their cytokines' profiles and expression of different chemokine receptors, that may differentially influence their migratory capacity. The present study examined the expression of matrix metalloproteinases, (MMP)-2 and MMP-9, by the two CD4 + Th cell subsets and the role of these proteases in their migration. We observed that migration of CD4 + T cells is dependent on the gelatinases, and that the migratory capacity of Th1 is higher than Th2 cells. In addition, Th1 in comparison to Th2 cells, from both human (healthy subjects and multiple sclerosis (MS) patients) as well as from murine origin, secrete higher levels of MMP-2 and MMP-9. These novel findings contribute to the understanding of the physiological Th1 and Th2 immune responses as well as the enhanced Th1 reactivity in immune-mediated diseases, such as MS, in which enhanced levels of MMP-2 and MMP-9 are associated with disease processes.